Chemical components from marine sponge Ianthella basta - Nhiem, Nguyen Xuan; Cuc, Nguyen Thi; Anh Tuan, Hoang Le; Thuy Hang, Dan Thi; Nam, Nguyen Hoai; Minh, Chau Van; Kiem, Phan Van (Vietnam Journal of Chemistry, 2014)
By various chromatographic separations, five known compounds, 24-oxocholesterol, indole-3-aldehyde, phenylacetic acid, thymidine, and deoxycytidine were isolated from the sponge Ianthella basta. Their structures were elucidated by spectroscopic methods and in comparison with the reported data. All compounds were isolated from this sponge for the first time. Keywords: Ianthella basta, Ianthellidae, 24-oxocholesterol, indole-3-aldehyde, phenylacetic acid.